2022
DOI: 10.1038/s41699-022-00317-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of sub-bandgap states in 2D halide perovskite single-crystal photodetector

Abstract: Greater stability of low-dimensional halide perovskites as opposed to their three-dimensional counterparts, alongside their high extinction coefficient and thus excellent emission properties, have made them popular candidates for optoelectronic applications. Topological edges are found in two-dimensional perovskites that show distinct electronic properties. In this work, using Kelvin Probe Force Microscopy, performed on butylammonium lead bromide (BA2PbBr4) single crystals with optical bandgap of ~413 nm, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…Figure S2 shows the I-V characteristics of the fabricated Au/RPP/Au photodetector at the dark and green-illumination conditions. The measured linear I-V characteristics reveal an ohmic contact between Au and RPP layer that is in agreement with the relating previous reports [7,[27][28][29][30][51][52][53]. On the other hand, the measured high dark current diminishes the detectivity for the realized Au/RPP/Au photodetector.…”
Section: Resultssupporting
confidence: 91%
“…Figure S2 shows the I-V characteristics of the fabricated Au/RPP/Au photodetector at the dark and green-illumination conditions. The measured linear I-V characteristics reveal an ohmic contact between Au and RPP layer that is in agreement with the relating previous reports [7,[27][28][29][30][51][52][53]. On the other hand, the measured high dark current diminishes the detectivity for the realized Au/RPP/Au photodetector.…”
Section: Resultssupporting
confidence: 91%
“…Owing to the same situation, similar results were observed for the BA 2 PbI 4 and BA 2 PbI 4 /BA 2 MAPb 2 I 7 perovskites, as shown in Figure 2 reported that high intensity XRD peaks of BA2MAPb2I7 crystals were obtained at the angles of 5.09°, 9.62°, 14.12°, 18.65°, 23.23°, 27.80° and 32.44° [33]. In addition, due to the continuity of the inorganic-organic-inorganic layer in the crystal structure of 2D OHP single crystals, the angle values at which XRD peaks increase regularly according to the d gap distance between the crystal planes [34][35][36]. Accordingly, the distance between the crystal planes of the synthesized 2D OHP single crystals was measured to be d=1.964nm and, using the Bragg equation (n𝜆 = 2𝑑𝑠𝑖𝑛𝜃), it was calculated that the difference between the angle values between each peak should be approximately 2𝜃=4.5°, which is consistent with the obtained results.…”
Section: Resultsmentioning
confidence: 95%
“…Such non-trivial electrical properties were attributed to a higher Fermi level of the terrace edges than the terraces, which renders a band bending at the terrace edges to accumulate the electrons . Later, such band bending and charge accumulation were also confirmed by Choi et al . The band bending at the terrace was visualized by the contact potential difference (CPD) characterization (Figure d,e).…”
Section: Excited-state Dynamics By Various Local Statesmentioning
confidence: 99%
“…E V is the valence band edge. Reproduced with permission from ref . Published by Springer Nature 2022.…”
Section: Excited-state Dynamics By Various Local Statesmentioning
confidence: 99%
See 1 more Smart Citation